Institutional choice in new democracies: Bargaining over Hungary's 1989 electoral law - BENOIT, Kenneth (Institutional Knowledge at Singapore Management University, 2001)
Institutions shape political outcomes, yet institutions themselves are endogenously shaped outcomes of political choices. Such choices are especially significant during transitions to democracy, when initial institutional designs fundamentally structure the path of democratic development. Most theories of institutional emergence, however, focus on stable contexts rather than on the conditions of acute uncertainty identified in the standard transitions literature. Our article attempts to bridge the two subfields by outlining and applying a model of institutional choice as the outcome of a struggle between fledgling opposition parties and the authoritarian regime wherein each side struggles to gain the greatest distributive payoff. We examine the creation of the Hungarian electoral system of 1989, linking the positions of the participants to the institutional alternatives which they expected to maximize their expected seat shares in the election to take place under those rules. The evidence shows that the individual parties generally preferred alternatives that maximized their expected seats, subject to the constraint of not derailing the negotiations as a whole. When a party had the possibility to reduce its uncertainty, it also tended to shift to a position reflecting its updated evaluation of an institutional alternative's effect on its expected seats. Far from being paralyzed by uncertainty and lack of information, actors in the choice of Hungary's 1989 electoral law were, with minor exceptions, able to effectively link institutional outcomes to electoral self-interest and to pursue these distributive gains through bargaining.